2021
DOI: 10.1140/epjc/s10052-021-09789-z
|View full text |Cite
|
Sign up to set email alerts
|

Generalised Ellis–Bronnikov wormholes embedded in warped braneworld background and energy conditions

Abstract: Ellis–Bronnikov (EB) wormholes require violation of null energy conditions at the ‘throat’. This problem was cured by a simple modification of the ‘shape function’, which introduces a new parameter $$m\ge 2$$ m ≥ 2 ($$m=2$$ m = 2 corresponds to the EB model). This leads to a generalis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Quasinormal modes, echoes and some other aspects of 4D-GEB spacetimes is reported in [43]. We recently suggested a further generalisation [65] where the 4D-GEB geometry is embedded in a five-dimensional warped spacetime and showed that energy conditions are satisfied even for m = 2 i.e. a novel 5D-EB geometry.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Quasinormal modes, echoes and some other aspects of 4D-GEB spacetimes is reported in [43]. We recently suggested a further generalisation [65] where the 4D-GEB geometry is embedded in a five-dimensional warped spacetime and showed that energy conditions are satisfied even for m = 2 i.e. a novel 5D-EB geometry.…”
mentioning
confidence: 87%
“…Though some recent research on wormholes embedded in higher-dimensional spacetime has been published [84][85][86][87][88][89], warped braneworld models have not been examined. We showed in [65] that a GEB (and EB) spacetime embedded in 5D warped bulk (5D-WWEB) model meets the energy conditions. As a follow-up, we analysed the timelike trajectories in these spacetimes in detail in [90].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular the quasinormal modes were studied. Also, this metric was recently studied in the context of the braneworld, where the authors in [63] embedding this solutions in a five dimensional warp braneworld and this brings the possibility to the weak energy condition being satisfied. The stability of these generalized solutions considering axial gravitational perturbations was made in [64].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several candidates have been proposed in the literature, for instance, wormholes in Einstein-Gauss-Bonnet theory [41], static wormhole solution for higher-dimensional gravity in vacuum [42], wormholes on braneworld [43,44,45,46], thin accretion disks in wormhole geometries [47], wormhole geometries in f (R)modified theories of gravity [48,49,50,52,52,53], wormhole models in f (R, T ) gravity theory [54,55], and some recent studies (see the ref. [56,57,58,59,60,61]). Furthermore, energy conditions play a significant role in the matter profiles of spacetime structure.…”
Section: Introductionmentioning
confidence: 99%